ANALYSIS OF SUPPLY CHAIN CRUDE PALM OIL (CPO) IN KUANTAN SINGINGI DISTRICT - Angga Pramana; Yelly Zamaya; Yelmira Zalfiatri (AGROINTEK, 2021)
The purpose of this study was to analyze the supply chain management of CPO in Kuantan Singingi a stream of goods (goods flow), the flow of money (money flow) and the flow of information (information flow), and knowing factors that affect the smoothness of the CPO supply chain. The research method used is descriptive qualitative. This study uses primary data and secondary data. Primary data is in the form of data obtained from the company, interviews with stakeholders (farmers, the Department of Agriculture, Association of Indonesian oil palm farmers and other parties), who are involved either directly or indirectly in the CPO supply chain in the company, while secondary data is in the form of journals and other documents. The flow of goods in the CPO supply chain consists of suppliers, including independent smallholders and smallholders who sell FFB to collectors. These company nuclei are directly brought to the palm oil mill. Then the factory processes the FFB into CPO and is sent to several companies that process derivative products. The financial flow starts from consumers to farmers in cash and non-cash. The flow of information begins from farmers to consumers who provide information in FFB selling prices and CPO prices. Transportation is one factor affecting the smooth supply chain of CPO in Kuantan Singingi District.